Simulações de campos de dunas sob a influência do crescimento de vegetação e da exposição do nível de água do terreno - Luna, Marco César Monteiro de Morais (2010)
In this work we study the genesis of coastal dune fields using the DUNE model developed by Sauermann et al. (2001) and Kroy et al. (2002), and later perfected by Schwämmle and Herrmann (2004). The model was developed to calculate the transport of grains by saltation and the formation of sand dunes, and then it takes account the growth of vegetation (Durán and Herrmann, 2006a). Initially we investigate the genesis and the early stages of development of coastal dune fields in the presence of vegetation growth. The model is applied to calculate the evolution of sand transported in the same direction of the wind into a land where there is vegetation growth. In previous work, the model reproduced the fixation of sand grains and the stabilization of dunes. Consequently, the barchans dunes in the presence of plants can be transformed into parabolic dunes (Durán et al., 2006a). Here, we seek the understanding of competition between the sand transport and vegetation growth in the development of transverse dunes under the influence of plant growth, when we find a maximum height for transverse dunes under the influence of vegetation. Then we conduct a detailed study of the development of dune fields taking into account changes in the relevant parameters: the width of the beach, availability of sand sediment, wind intensity, the vegetation growth rate and the maximum height reached by the plants. Different morphologies are obtained for the coastal dune fields which depend crucially on the characteristic vegetation growth rate and the wind shear velocity, which can reproduce patterns found in actual fields. After we investigate, the genesis and development of coastal dune fields in the presence of a dynamic water level. In other to do it we complement this model with a dynamic water surface. Here we try to obtain and understand the influence of a exposed water surface over the ground in the development and morphology of the dunes. In this way, we also try a quantitative understanding of the dynamics of coastal dune fields as a function of local climatic conditions, since the dynamics of the water level is linked to rainfall (Jimenez et al., 1999, Levin et al., 2009). The results show that for a constant wind shear velocity u∗ the main effect of the presence of water is to produce the dunes in the field more regular in their shape and size. As the shift Aw in the water level becomes larger, the dunes undergo a transition from barchans dunes to chains of barchans dunes, and then to transverse dunes, reducing the maximum height reached by the dunes in the field. The water spreads the sand across the field and reduces the existence of areas which are free of the sand presence, preventing the formation of dunes and leading to the formation of a sandy bed with a smooth surface. When we increase the time which the water level tew is above the ground, the dunes in the field pattern are more regular in shape and height in the same way as when we increase the shift in water level. For a unidirectional wind sinusoidally oscillating out of phase with respect to fluctuation of water level, in opposition to the constant wind, as Aw becomes larger, higher are the dunes in the field, and they undergo a transition from chains of barchans dunes to isolated barchans dunes. In this case, the sand is retained in the dunes and we do not observe the formation of a sand bed as Aw grows. In the case of a sinusoidal wind in phase with the oscillation of the water level, the dunes appear only for small shifts in the water level. These results agree with the observations of real sand dune fields (Kocurek et al., 1992), reproducing the constructive and destructive phases which alternate in dune fields under the influence of an oscillating water level due to seasonal climatic changes. In the simulations we reproduce some morphological patterns of sand dunes that are found in the Lençóis Maranhenses sand dune field. Comparison between simulation results and satellite images of this region is quite satisfactory from a qualitative point of view and from a quantitative point of view.